The effect of smoking on gingival crevicular fluid peptidoglycan recognition protein‐1 level following initial periodontal therapy in chronic periodontitis - Karsiyaka Hendek, Meltem; Kisa, Ucler; Olgun, Ebru (Oral diseases, 2020)
Objective To determine the effect of smoking on peptidoglycan recognition protein (PGRP)‐1 levels in gingival crevicular fluid (GCF) in smokers and non‐smokers with chronic periodontitis (CP) following initial periodontal therapy. Subjects and Methods A total of 40 patients with CP (20 smokers (S + CP) and 20 non‐smokers (S‐CP)) and 40 subjects with healthy periodontium (20 smokers (S + PH) and 20 non‐smokers (S‐PH)), comprising 80 subjects, were included in this study. Baseline GCF samples were obtained from all subjects, and clinical periodontal measurements were recorded. In patients who had received initial periodontal therapy, GCF samples were obtained and all clinical periodontal measurements were recorded again during the 6th–8th weeks. GCF PGRP‐1 levels were analyzed by enzyme‐linked immunosorbent assay. Results At baseline, GCF PGRP‐1 levels were significantly higher in both groups with CP than in both groups with healthy periodontium, whereas these levels were significantly lower in S + CP than in S‐CP. GCF PGRP‐1 levels decreased significantly in both CP groups after periodontal therapy, and this reduction was significantly greater in non‐smokers than in smokers. Conclusion Smoking might have a suppressive effect on GCF PGRP‐1 levels in CP. Initial periodontal therapy is effective in decreasing GCF PGRP‐1 levels in both smokers and non‐smokers with CP.